밀웜 분말을 첨가한 머핀의 영양적 기능 및 품질 특성 - 윤진아(Jin A Yoon); 신경옥(Kyung-Ok Shin) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구는 밀웜을 첨가하여 머핀을 제조하고, 머핀의 품질특성 및 항산화 활성을 확인하여 밀웜의 기능성 식품으로서의 가치를 알기 위해 실시하였다. 대조군에 비해 밀웜 분말 10% 첨가군부터 머핀의 색상은 갈색으로 변하였으며, 이는 밀웜 분말의 첨가량이 증가할수록 색상이 진하게 나타났다. 색도 중 L값과 b값은 낮아지고, a값은 증가하는 경향을 보였다. 경도는 대조군에서 23.33±6.35, 밀웜 분말 5%와 10% 첨가군에서 각각 26.67±4.04, 26.00±4.36을 보였다. 머핀의 밀웜 분말 함량이 증가할수록 조단백질 함량, 마그네슘 함량, 총 페놀 함량 및 ABTS 라디칼 소거 활성은 유의하게 증가하였다(P<0.05). 따라서 밀웜의 다양한 영양학적인 기능과 항산화 활성을 이용하여 기능성 식품 소재로서의 가치가 있을 것으로 판단되며, 10% 정도의 밀웜 분말을 사용하여 머핀 제조에 활용하면 영양 측면이 강조된 상품이 될 것으로 판단된다. In this study, muffins were prepared by adding varying concentrations of mealworms, and the quality characteristics and antioxidant activity of the muffins were confirmed. Compared to the control group, supplementation with 10% mealworm powder changed the color to brown. Among the chromaticities evaluated, the L and b values decreased, and the a value tended to increase with increasing mealworm amounts. The crude protein content, magnesium content, total phenol content, and ABTS radical scavenging activity were also significantly increased (P<0.05) with increased mealworm supplementation. Thus, considering the various nutritional functions and antioxidant activity, mealworm is valuable as a functional food material. Emphasizing the nutritional aspects, we propose the application of about 10% mealworm powder in the manufacturing of muffins. KCI Citation Count: 1